High-contrast in vivo fluorescence imaging exploiting wavelengths beyond 1880 nm - Jiayi Li; Qiming Xia; Tianxiang Wu; Yuhuang Zhang; Shiyi Peng; Yifei Li; Yixuan Li; Hui Lin; Mingxi Zhang; Jun Qian (Nature Communications)
Abstract The second near-infrared (NIR-II) window is widely acknowledged for its excellent potential in in vivo fluorescence imaging. Currently, NIR-II fluorescence imaging predominantly operates within the 900-1880 nm spectral range, while the region beyond 1880 nm has been disregarded due to the large light absorption of water. Based on a refined understanding of the effect of light absorption on imaging, we propose an approach that utilizes the previously neglected region surrounding the water absorption peak at ~1930 nm for imaging. Both simulations and experiments confirm that the water absorption contributes positively to imaging, enabling high-contrast in vivo fluorescence imaging in the 1880-2080 nm window. To further assess the applicability of this approach in different biological media, we extend our focus to fluorescence imaging in adipose tissue. This leads to the expansion of the imaging window to 1700-2080 nm, owing to the unique light absorption characteristics of adipose tissue. Our results demonstrate that the 1700-2080 nm region provides optimal imaging quality in adipose tissue, attributing to its moderate absorption and low scattering. This work advances our understanding of the interplay between light absorption and photon scattering in bioimaging, providing an insight for selecting optimal imaging windows to achieve high-contrast fluorescence imaging.